2006
DOI: 10.1007/s10545-006-0096-3
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of phenylalanine variations under tetrahydrobiopterin load in subjects affected by phenylalanine hydroxylase deficiency

Abstract: A fall in blood phenylalanine (Phe) after tetrahydrobiopterin (BH(4)) administration is a common trait in phenylalanine hydroxylase (PAH, EC 1.14.16.1) deficiency (McKusick 261600). To explore the extent and biological correlates of this phenomenon we studied: (a) the spectrum of BH(4) response in patients with PAH deficiency; (b) the variability of BH(4) response according to the severity of the biochemical phenotype; and (c) the variability of the response to BH(4) in subjects with the same genotype. Fifty P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
2
34
1
Order By: Relevance
“…Previous reports cite a BH 4 responsiveness of 30-45% in the general PKU population, with reported associations to clinical phenotype and the frequency of responsive cases being 80-100% for mild HPA, 40-60% for mild PKU and o10% for classical PKU. 21,[38][39][40] Most of the patients in the current study who showed BH 4 responsiveness suffer from mild PKU or mild HPA; these patients responded to BH 4 loading and showed an increase in in vivo PAH activity by phenylalanine breath test, 15,31 which is proportional to the residual PAH activity by BH 4 dosing under the regulation system of BH 4 and phenylalanine in in vivo PAH activity. 31,41 Therefore, a residual PAH activity resulting from a combination of both alleles is useful to predict the BH 4 responsiveness in PKU patients.…”
Section: Genotypes and Bh 4 Responsiveness In Pku Y Okano Et Almentioning
confidence: 63%
“…Previous reports cite a BH 4 responsiveness of 30-45% in the general PKU population, with reported associations to clinical phenotype and the frequency of responsive cases being 80-100% for mild HPA, 40-60% for mild PKU and o10% for classical PKU. 21,[38][39][40] Most of the patients in the current study who showed BH 4 responsiveness suffer from mild PKU or mild HPA; these patients responded to BH 4 loading and showed an increase in in vivo PAH activity by phenylalanine breath test, 15,31 which is proportional to the residual PAH activity by BH 4 dosing under the regulation system of BH 4 and phenylalanine in in vivo PAH activity. 31,41 Therefore, a residual PAH activity resulting from a combination of both alleles is useful to predict the BH 4 responsiveness in PKU patients.…”
Section: Genotypes and Bh 4 Responsiveness In Pku Y Okano Et Almentioning
confidence: 63%
“…Other factors that could contribute to an inconsistency in our findings could include once again the limited methodology with unmonitored changes in diet or other external factors such as intercurrent illness (Burton et al 2007) and variability between individuals that may reflect sapropterin absorption and pharmacokinetics or bioavailability of the cofactor in the individual patient (Fiege et al 2004;Leuzzi et al 2006;Nielsen et al 2010;Shintaku et al 2005). Meanwhile, studying the residual PAH activity arising from the interaction of the mutant PAH subunits, carried by the PKU patients, is essential and may also influence BH 4 -responsiveness.…”
Section: Discussionmentioning
confidence: 94%
“…A decrease of Phe of 30 %, compared to pre-BH 4 level, was deemed to be clinically significant (Mitchell et al 2005). Patients are classed as 'positive' if they reached a decrease of 30% after 8 h, 'intermediate' if a decrease of 30 % was observed at 32 h or at the 7th day and 'negative' if no decrease of 30% or greater was observed at any point (Leuzzi et al 2006), but one of our patient's homozygous for this mutation was not responsive (data not shown). The other discrepant results were observed (patients #50 and #55).…”
Section: Resultsmentioning
confidence: 99%